Subject indexing of normative acts - Pirronitto, Ignazio (JLIS.it : Italian journal of library and information science, 2024)
Subject indexing can be related to normative acts in the development of semantic metadataction aimed at not-book resources. The survey demonstrates how the indexing process by subject can be applied to this special type of resources, so as to facilitate their management in a knowledge organization. The study attempts to apply the Italian system of subject indexing in each of its steps, and practical examples are suggested on how to provide semantic access points that enable the search for regulatory acts by subject. A specific in-depth study is devoted to bringing out all the semantic aspects that can be considered with regards to the subject of a norm and how this can be declined in order to bring out firstly, what the “aboutness” of the resource is, secondly, what the “isness” of a normative act is, and finally, what is required to create strings of subject built based on the “ofness” of the resource.